The chromatin remodeling factor CHD7 controls cerebellar development by regulating reelin expression - Whittaker, Danielle E. (2017)
The mechanisms underlying the neurodevelopmental deficits associated with CHARGE syndrome, which include cerebellar hypoplasia, developmental delay, coordination problems, and autistic features, have not been identified. CHARGE syndrome has been associated with mutations in the gene encoding the ATP-dependent chromatin remodeler CHD7. CHD7 is expressed in neural stem and progenitor cells, but its role in neurogenesis during brain development remains unknown. Here we have shown that deletion of Chd7 from cerebellar granule cell progenitors (GCps) results in reduced GCp proliferation, cerebellar hypoplasia, developmental delay, and motor deficits in mice. Genome-wide expression profiling revealed downregulated expression of the gene encoding the glycoprotein reelin (Reln) in Chd7-deficient GCps. Recessive RELN mutations have been associated with severe cerebellar hypoplasia in humans. We found molecular and genetic evidence that reductions in Reln expression contribute to GCp proliferative defects and cerebellar hypoplasia in GCp-specific Chd7 mouse mutants. Finally, we showed that CHD7 is necessary for maintaining an open, accessible chromatin state at the Reln locus. Taken together, this study shows that Reln gene expression is regulated by chromatin remodeling, identifies CHD7 as a previously unrecognized upstream regulator of Reln, and provides direct in vivo evidence that a mammalian CHD protein can control brain development by modulating chromatin accessibility in neuronal progenitors.